The Impact of Human Relations and Work Appreciation on Improving Employee Performance at The Department of Population and Civil Registration of Bogor Regency - Dhiya Fauziah; Nazifah Husainah (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2025)
The purpose of this study is to examine the influence of human relations and work appreciation on employee performance at the Department of Population and Civil Registration of Bogor Regency. This research uses a quantitative associative method aimed at identifying the effect of dependent variables on independent variables. The results of this study provide up-to-date information regarding the influence of human relations and work appreciation on employee performance. The findings offer new insights into the importance of fostering good relationships among employees and providing work appreciation to create a positive impact on employee performance.